ANALYSIS OF THE INFLUENCE OF COMMUNITY PARTICIPATION AND SUPPORTING FACTORS ON THE EFFECTIVENESS OF FISHERY RESOURCE MANAGEMENT - Aisyah, Siti; Lanin, Dasman (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2024)
Sustainable fisheries resource management is a major challenge, especially in a maritime country like Indonesia, which has abundant fisheries potential but often experiences problems such as overfishing and ecosystem damage. Community participation, education level, access to information, government policy support, and the existence of local institutions are believed to influence the effectiveness of such management. This study aims to analyze the influence of these factors on the effectiveness of fisheries resource management. The method used is multiple regression to identify the relationship between independent variables and dependent variables. The results of the study indicate that all factors studied have a positive and significant effect on the effectiveness of fisheries resource management, with community participation and access to information having a very large influence. This study provides important insights for policy makers to strengthen these factors in order to improve the effectiveness and sustainability of fisheries resource management